Effect of pH, heat treatment and enzymes on the antifungal activity of lactic acid bacteria against Candida species - Bulgasem, BY; Hassan, Z; Omar, RHA; Lani, MN; Alshelmani, MI; Nur Huda Faujan (Malaysian Soc Microbiology, 2024)
Indexed by WOS/ Scopus